How Strong Buyers Spur Upstream Innovation - Roman Inderst; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
We challenge the view that the presence of powerful buyers stifles suppliers incentives to innovate. Following Katz (1987), we model buyer power as buyers ability to substitute away from a given supplier and isolate several effects that support the opposite view, namely that the presence of powerful buyers induces a supplier to invest more in cost reduction. In contrast in negotiations with smaller buyers, the outcome of negotiations with large buyers is fully determined by their more valuable alternative supply option. This increases the suppliers incentives to reduce marginal costs, both as the supplier receives a larger fraction of the thereby generated incremental profits and as this makes buyers alternative supply option less valuable. The latter effect is due to downstraem competition between buyers and, as we show, is also stronger the larger and thus the more powerful buyers are.
Keywords: 330; Buyer power; Merger; Investment Incentives; Nachfragemacht; Betriebliche Investitionspolitik; Innovation; Fusion; Mathematische Ökonomie